Exendin-4 ameliorates tau hyperphosphorylation and cognitive impairment in type 2 diabetes through acting on Wnt/β-catenin/NeuroD1 pathway - Xiaonan Kang; Dan Wang; Lu Zhang; Teng Huang; Siyue Liu; Xiaohui Feng; Yaoyao Guo; Ziyin Zhang; Zhongjing Wang; Huihui Ren; Gang Yuan (BMC, 2023)
Abstract Background  Type 2 diabetes (T2D) is an independent risk factor for Alzheimer's disease (AD). Exendin-4 (Ex-4), a widely used glucagon-like peptide-1 receptor agonist drug in the treatment of T2D, has been demonstrated the therapeutic effects on diabetic encephalopathy (DE). Especially, the Ex-4 ameliorates the tau hyperphosphorylation and cognitive impairment in DE. And these crucial alterations are also important bridge between T2D and AD. However, its unique mechanism is unclear. Methods  The db/db mice, high-fat-diet (HFD) / streptozotocin (STZ)-induced diabetic (HF-diabetic) mice, and high-glucose-damaged (HGD) HT-22 hippocampal cells were enrolled to examine the effects of Ex-4 on AD-like changes in T2D. The Novel object recognition test (NORT) and Morris water maze test (MWMT) were conducted to evaluate the cognitive impairment. The Dickkopf-1 (DKK1) was employed to weaken the activation of the Wnt/β-catenin pathway to explore the mechanism of Ex-4 in protecting the brain functions. The JASPAR was based to predict the interaction between NeuroD1 and the promoter region of Ins2. Moreover, the chromatin immunoprecipitation coupled with quantitative polymerase chain reaction (ChIP-qPCR) and luciferase reporter assays were performed. Results  Ex-4 alleviated the tau hyperphosphorylation, increased the brain-derived insulin, and improved the PI3K/AKT/GSK3-β signalling in db/db mice, HF-diabetic mice, and HGD HT-22 hippocampal neuronal cells. The NORT and MWMT indicated that Ex-4 alleviated the learning and memory deficits in HF-diabetic mice. The inhibitor Dickkopf-1 (DKK1) of the Wnt/β-catenin pathway significantly blocked the protective effects of Ex-4. Regarding further molecular mechanisms, NeuroD1 was affected by Ex-4 in vivo and in vitro, and the knockdown or overexpression of NeuroD1 suggested its crucial role in promoting the brain insulin by Ex-4. Meanwhile, the ChIP‒qPCR and luciferase reporter assays confirmed the combination between NeuroD1 and the promoter region of the insulin-encoding gene Ins2. And this interaction could be promoted by Ex-4. Conclusions Our study proposes that Ex-4 alleviates tau hyperphosphorylation and cognitive dysfunction by increasing Ins2-derived brain insulin through the Wnt/β-catenin/NeuroD1 signaling in T2D. And its also show new lights on part of the progress and mechanism on treatment targets for the DE in T2D.